Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1001/archsurg.2009.112
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lymph Node Evaluation With Colorectal Cancer Resection

Abstract: Increased LN retrieval does not identify a greater number of patients with stage III CRC nor does it increase the proportion of patients with positive LNs with N2 disease. Our data suggest that harvest of at least 12 LNs as a quality or performance measure appears unfounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…In this regard, for over 20 years the "magic number" [17] 12 has always been considered the minimum number of lymph nodes to be sampled, which would allow for a correct diagnosis of "N0" in 90% of cases of colorectal cancer. However, this range is as a today considered "uncommon" or "not, adequate" or achievable only in specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, for over 20 years the "magic number" [17] 12 has always been considered the minimum number of lymph nodes to be sampled, which would allow for a correct diagnosis of "N0" in 90% of cases of colorectal cancer. However, this range is as a today considered "uncommon" or "not, adequate" or achievable only in specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the proportion of patients with colorectal cancer undergoing surgery at community hospitals who had at least 12 lymph nodes examined increased from 53.0% from 1996 to 2004 to 71.6% from 2005 to 2007. 12 More broadly (ie, not only at community hospitals), the Agency for Healthcare Research and Quality 2010 National Healthcare Quality Report showed improvements over time for a number of cancer-related quality measures, including the proportion of adults receiving colorectal cancer screening, the proportion of adults diagnosed with colorectal cancer at regional or distant stages, and the proportion of patients with colorectal cancer undergoing surgical resection who had at least 12 lymph nodes examined. 13 Beyond the secular trends observed in quality-of-care improvements during this time period, use of the CoC RQRS also likely increased concordance with the quality measures of this evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increased number of evaluated nodes did not lead to better staging. A large study by Kukreja et al [18] has failed to demonstrate an increase in the proportion of stage III patients following an initiation of a program that increased significantly the number of patients with 12 or more evaluated nodes. They have concluded that harvesting of at least 12 nodes as a quality or performance measure appeared unfounded.…”
Section: Discussionmentioning
confidence: 99%
“…The adequacy of a lower threshold of evaluated nodes may reflect the fact that further examination of the specimen for lymph nodes following an adequate surgery would focus on smaller mesenteric nodes located away from the primary tumor that are less likely to contain disease [18].…”
Section: Discussionmentioning
confidence: 99%